U-Pb zircon geochronology and Sr-Nd isotopic composition of the Inchope orthogneiss in Mozambique: Age constraints and petrogenetic implications. (July 2017) - Manjate, Vicente Albino
Abstract: The Inchope orthogneiss comprises a mesoproterozoic group of variously deformed and migmatised orthogneisses in the Chimoio group. This area is well known for its numerous, small pegmatite deposits with cassiterite and columbite. Zircon U-Pb geochronological and whole rock Sr-Nd isotope data are reported for five Inchope orthogneiss samples. The zircon U-Pb data exhibit one period of crystallization between 1065 and 1053 Ma and two metamorphic ages of 956 Ma and 484 Ma. The Inchope orthogneiss displays evolved Nd isotopic compositions with ɛNdi between −11.7 and −13.3, 87 Sr/ 86 Sri between 0.7117 and 0.7209 and TDM values of between 2.3 and 2.4 Ga. Therefore, the Inchope orthogneiss crystallized in Mesoproterozoic from the paleoproterozoic metapelites along the eastern margin of the archaen Zimbabwean craton. This was followed by pegmatite veins intrusions and Pan-African tectonometamorphic reworking. These features are typical of S-type and calc-alkaline granites in continental margin arcs. Graphical abstract: Highlights: The Inchope orthogneiss crystallized in Proterozoic from a hybrid source dominated by crustal material. The Inchope orthogneiss was affected by two metamorphic events. The first metamorphic age is related to pegmatite veins intrusion. The second metamorphic age is related to Pan-African deformation.